FOREIGN EXPERIENCE IN LICENSING THE PHARMACEUTICAL INDUSTRY - Yokubova U. M. (Journals Park Publishing, 2023)
The purpose of this study is to compare the regulations governing the licensing of the pharmaceutical industry in foreign countries.
Keywords: Licensing, license, pharmaceutical activity, pharmacy, pharmacist, medicines.